PERFECTION OF MOTHERS AND CHILDREN SERVICE AT MODERN STAGE - O.V. Chumakova; O.S. Filippov; E.V. Guseva; A.A. Khodunova; S.R. Konova; V.N. Sadovnikova ("Paediatrician" Publishers LLC, 2008)
The dynamics of rates of maternal, infant and perinatal mortality in Russian federation is presented in this article. The reasons of infant mortality were analyzed. The results of realization of federal principal program «children of Russia» and subprogram «healthy child» in 2003-2006 years, and measures of priority state project in health service sphere in directions «neonatal screening» and «delivery certification» were given. For the purpose of further decrease of rates of maternal and infant mortality it is necessary to strengthen a material and technical basis of institutions of maternity and childhood, to create a system of perinatal centers, to raise an accessibility of high tech types of medical service, to organize training of personnel, to develop a prophylactic direction of medical service.Key words: maternal mortality, infant mortality, neonatal screening, high tech medical service.